2020
DOI: 10.1038/s41598-020-75668-4
|View full text |Cite
|
Sign up to set email alerts
|

Operando direct observation of spin-states and charge-trappings of blue light-emitting-diode materials in thin-film devices

Abstract: Spin-states and charge-trappings in blue organic light-emitting diodes (OLEDs) are important issues for developing high-device-performance application such as full-color displays and white illumination. However, they have not yet been completely clarified because of the lack of a study from a microscopic viewpoint. Here, we report operando electron spin resonance (ESR) spectroscopy to investigate the spin-states and charge-trappings in organic semiconductor materials used for blue OLEDs such as a blue light-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…We have focused on electron spin resonance (ESR) spectroscopy as an analysis method. The ESR spectroscopy is useful because it can conduct nondestructive measurements during device operation (operando) and microscopically observe the charge states in the cells at the molecular level. ,, In particular, by using operando ESR spectroscopy, we have demonstrated the correlation between the photodeterioration of solar-cell parameters such as J SC and V OC and photogenerated hole accumulation in a typical polymer solar cell with blend films of P3HT and [6,6]-phenyl-C 61 -butyric acid methyl ester (PC 61 BM), ,, high-efficiency polymer solar cells with blend films of a donor–acceptor (D–A) conjugated copolymer poly­({4,8-bis­[(2-ethylhexyl)­oxy]­benzo­[1,2- b :4,5- b ′]­dithiophene-2,6-diyl}­{3-fluoro-2-[(2-ethylhexyl)­carbonyl]­thieno­[3,4- b ]­thiophenediyl}) (PTB7) or a PTB7 derivative poly­[4,8-bis­(5-(2-ethylhexyl)­thiophen-2-yl)­benzo­[1,2- b ;4,5- b ′]­dithiophene-2,6-diyl- alt -(4-(2-ethylhexyl)-3-fluorothieno­[3,4- b ]­thiophene)-2-carboxylate-2-6-diyl] (PTB7-Th) and [6,6]-phenyl-C 71 -butyric acid methyl ester (PC 71 BM), and a highly durable polymer solar cell with blend films of poly­[naphtho­[1,2- c :5,6- c ′]­bis­[1,2,5]­thiadiazole-5,10-diyl­[3,4′-bis­(2-butyloctyl)­[2,2′-bithiophene]-5,5′-diyl]­thiazolo­[5,4- d ]­thiazole-2,5-diyl­[3′,4-bis­(2-butyloctyl)­[2,2′-bithiophene]-5,5′-diyl]] (PTzNTz) and PC 71 BM . In this study, OSCs were fabricated using polymers with different end structures, and the accumulated charge states were directly observed by operando ESR spectroscopy to investigate the correlation between the end structures of polymers and the time durability of solar cells with these polymers in detail.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on electron spin resonance (ESR) spectroscopy as an analysis method. The ESR spectroscopy is useful because it can conduct nondestructive measurements during device operation (operando) and microscopically observe the charge states in the cells at the molecular level. ,, In particular, by using operando ESR spectroscopy, we have demonstrated the correlation between the photodeterioration of solar-cell parameters such as J SC and V OC and photogenerated hole accumulation in a typical polymer solar cell with blend films of P3HT and [6,6]-phenyl-C 61 -butyric acid methyl ester (PC 61 BM), ,, high-efficiency polymer solar cells with blend films of a donor–acceptor (D–A) conjugated copolymer poly­({4,8-bis­[(2-ethylhexyl)­oxy]­benzo­[1,2- b :4,5- b ′]­dithiophene-2,6-diyl}­{3-fluoro-2-[(2-ethylhexyl)­carbonyl]­thieno­[3,4- b ]­thiophenediyl}) (PTB7) or a PTB7 derivative poly­[4,8-bis­(5-(2-ethylhexyl)­thiophen-2-yl)­benzo­[1,2- b ;4,5- b ′]­dithiophene-2,6-diyl- alt -(4-(2-ethylhexyl)-3-fluorothieno­[3,4- b ]­thiophene)-2-carboxylate-2-6-diyl] (PTB7-Th) and [6,6]-phenyl-C 71 -butyric acid methyl ester (PC 71 BM), and a highly durable polymer solar cell with blend films of poly­[naphtho­[1,2- c :5,6- c ′]­bis­[1,2,5]­thiadiazole-5,10-diyl­[3,4′-bis­(2-butyloctyl)­[2,2′-bithiophene]-5,5′-diyl]­thiazolo­[5,4- d ]­thiazole-2,5-diyl­[3′,4-bis­(2-butyloctyl)­[2,2′-bithiophene]-5,5′-diyl]] (PTzNTz) and PC 71 BM . In this study, OSCs were fabricated using polymers with different end structures, and the accumulated charge states were directly observed by operando ESR spectroscopy to investigate the correlation between the end structures of polymers and the time durability of solar cells with these polymers in detail.…”
Section: Introductionmentioning
confidence: 99%
“…We used a lock-in detection method for the ESR measurements with a modulation frequency of 100 kHz for the external magnetic field. Thus, we could observe long-lived charges (spins) with a lifetime of >10 μs or accumulated charges in the OLEDs, and cannot observe charges with a lifetime of <10 μs that contribute the standard operation of the OLEDs [28][29][30][31][36][37][38][39][40] . We measured operando ESR signals while increasing Vbias from 0 V to 10 V in 0.5 V increment.…”
Section: Oled Device Structures and Characterization Methodsmentioning
confidence: 99%
“…So far, we have been studying microscopic nature such as electric charge states, electron spin states, and molecular orientations in organic devices, etc. using the ESR method [28][29][30][31][32][33][34][35][36][37][38][39] . We have reported an operando ESR study of OLEDs with Alq3, which have shown the correlation between intrinsic luminescence deterioration and electric charge states at the molecular level 28 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deep blue TADF materials are still a focused-on area. Blue OLED emitters need to satisfy the criteria of wide bandgap generally, between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) energy levels, making it challenging to achieve highly efficient and pure blue emission [15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, deep blue TADF materials are still a focused-on area. Blue OLED emitters need to satisfy the criteria of wide bandgap generally, between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) energy levels, making it challenging to achieve highly efficient and pure blue emission [15]. Because of this, in 2016, Hatakeyametal et al, first proposed a new structure of BNdoped multi-resonance (MR) TADF molecule, the DABNA-1 (Figure 1a), with blue emission at 462 nm, and the FWHM of 28 nm [16].…”
Section: Introductionmentioning
confidence: 99%